1998
DOI: 10.1074/jbc.273.47.31160
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Leptin Regulates Hepatic but Not Peripheral Glucose Fluxes

Abstract: ). Here we examine whether intracerebroventricular (ICV) leptin administration regulates peripheral and hepatic insulin action. Recombinant mouse leptin (n ‫؍‬ 14; 0.02 or 1 g/kg⅐h) or vehicle (n ‫؍‬ 9) were administered ICV for 6 h to conscious rats, and insulin action was determined by insulin (3 milliunits/kg⅐min) clamp and tracer dilution techniques. During physiologic hyperinsulinemia (ϳ65 microunits/ml), the rates of glucose uptake (R d , 20.1 ؎ 0.6 and 23.1 ؎ 0.7 versus 21.7 ؎ 0.6 mg/kg⅐min; p ‫؍‬ NS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
174
2
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(190 citation statements)
references
References 45 publications
(82 reference statements)
9
174
2
5
Order By: Relevance
“…[13][14][15][16] We found that chronic central administration of leptin decreased fasting plasma glucose concentrations, a finding consistent with previous results showing that chronic central administration of leptin decreased fasting plasma glucose levels in normal and diabetic rats. 20 Centrally administered leptin has also been shown to stimulate glucose uptake to the peripheral tissue 13,14 and to increase glucose turnover, 15 which may result in decreased plasma glucose levels.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…[13][14][15][16] We found that chronic central administration of leptin decreased fasting plasma glucose concentrations, a finding consistent with previous results showing that chronic central administration of leptin decreased fasting plasma glucose levels in normal and diabetic rats. 20 Centrally administered leptin has also been shown to stimulate glucose uptake to the peripheral tissue 13,14 and to increase glucose turnover, 15 which may result in decreased plasma glucose levels.…”
Section: Discussionsupporting
confidence: 81%
“…Central administration of leptin suppresses insulin secretion from the pancreas, 12 increases glucose uptake in peripheral tissues, and modulates hepatic glucose production. [13][14][15][16] Chronic intracerebroventricular (ICV) administration of ghrelin has been reported to increase the 24-h respiratory quotient without altering energy expenditure or locomotor activity. 3 It is not clear, however, if these alterations are associated with the changes in body weight and fat mass resulting from ICV administration of ghrelin.…”
Section: Introductionmentioning
confidence: 99%
“…Whether these actions of leptin are mediated directly or indirectly, however, remains controversial. For example, a redistribution of hepatic glucose flux occurs after intracerebroventricular injection of leptin, suggesting a central and indirect action of leptin on liver (13). However, peripheral administration of leptin (13) and studies with isolated perfused liver (38) indicate the possibility of a direct action of leptin on this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Using [ 13 C]NMR, Cohen et al (50) have shown that leptin can acutely enhance hepatic glycogen synthesis in vivo, and leptin has been shown to enhance glycogen synthesis in isolated hepatocytes (51). This latter effect, however, seems to occur via an inhibition of phosphorylase rather than an increase in synthase activity (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation